PENGARUH UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA - RR. SRI HANDAYANI; AGUSTONO DWI RACHADI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2009)
This study investigated size effect to earnings management. In this study, it is investigated whether medium and large-sized firm more aggressive to use earnings management through reporting positive earnings to avoid losses and/or earnings decreases by examining the earnings (change) frequency distribution and probit analysis. Docu-mented is empirical evidence that small-, medium-and large-sized firms tend to report positive earnings to avoid earnings losses. However, this study observed that firm size plays differing roles in earnings management. This study found that medium-and large-sized firms do not engage more earnings management aggressively than small firms for both avoiding reporting earnings losses and earnings decreases.